2020
DOI: 10.1002/srin.202000182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blast Furnace Operation Modes in the World

Abstract: Figure 11. Injection practices in different regions of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Die betrieblich erreichte Realfahrweise des Hochofenprozesses liegt nur um 7 % höher als der undurchführbare Idealzustand. Der Hochofen wird, zumindest in Deutschland, demnach mit einem Wirkungsgrad von etwa 93 % betrieben .…”
Section: Wertschöpfung In Der Stahlindustrieunclassified
“…Die betrieblich erreichte Realfahrweise des Hochofenprozesses liegt nur um 7 % höher als der undurchführbare Idealzustand. Der Hochofen wird, zumindest in Deutschland, demnach mit einem Wirkungsgrad von etwa 93 % betrieben .…”
Section: Wertschöpfung In Der Stahlindustrieunclassified
“…Counter to our expectations, no statistically significant time trend was found that would indicate longer campaigns of more modern blast furnaces (Figure 3C). One explanation for this finding could be that while the technical lifetime of a blast furnace has increased in recent decades, 41 more blast furnaces are relined early due to changing economic circumstances, including potentially accelerated technological innovation cycles. Campaign life was also found to be largely independent from furnace size (Figure 3D).…”
Section: Blast Furnace Campaign Lifementioning
confidence: 99%
“…This is in line with reports on world record blast furnace campaigns of 30-35 years. 41,62 For reported campaigns between 30 and 35 years, we tried to find relining information through a web-based search. Through this, we could find additional relining dates that were missing in the data for four furnaces.…”
Section: Historic Campaign Lifementioning
confidence: 99%
“…The actual mode of operation of the blast furnace process is only 7 % higher than the impracticable ideal state. The blast furnaces at least in Germany are therefore operated with an efficiency level of roughly 93 % .…”
Section: Steel Industry Value Chainmentioning
confidence: 99%